THE EUCHARISTIC CONTEXT OF PASTORAL RESPONSE TO CONTEMPORARY CHALLENGES IN MARRIAGE, FAMILY, AND SEXUALITY - LEMASTERS, Philip (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2018)
Pastoral ministry in the Orthodox Church on matters of marriage, sexuality, and family must focus on helping parishioners embrace the full meaning of a one flesh union with Jesus Christ in the Eucharist. The one flesh relationship of marriage must be oriented through the blessing of the Church toward the eschatological fulfilment of the Kingdom of God. The connections of Eucharist and matrimony are so profound that pastoral ministry must guide parishioners to enter into only those marriages that may be blessed in the Church as signs of the communion of a man and a woman with Christ.